Biological and taxonomical characteristics of endophytic Streptomyces TQR8-14 and its production potential of antimicrobial substance - Thao, Phan Thi Hong; Linh, Nguyen Vu Mai; Lien, Nguyen Thi Hong; Hieu, Nguyen Van (Vietnam Journal of Biotechnology, 2018)
Endophytic actinomycetes colonize in living plant tissues without causing harm to the host plant. In fact, they are regarded as effective bio-control agents and plant growth promoters due to their ability to activate plant self-immunity and produce biologically active secondary metabolites. Recent studies reported higher rates in finding new strains and antimicrobial substances among endophytes than actinomycetes from soil and plant surface. In this work, endophytic actinomycetes were isolated from Ham Yen orange trees, a famous specialty of Tuyen Quang province, and screened for antimicrobial activity against plant pathogenic bacteria and fungi. The isolate TQR8-14, showing strong activity, was studied with regard to its biological and taxonomical characteristics and production of antimicrobial substance. Based on the mycelial morphology, this isolate was placed in yellow group of streptomycetes. The isolate developed milky to yellow aerial mycelia on all test media and long straight spore chains bearing smooth cylinder spores. The isolate could grow at wide range of temperature 15 to 45oC, of pH 4 to 10; on substrates such as carboxy methyl cellulose, starch, protein and chitin; and tolerated up to 3% salinity. Its 16S rDNA nucleotide sequence (1,404 bp) shared 99% similarity to Streptomyces parvus. Therefore, the isolate was named as Streptomyces parvus TQR8-14. The highest antimicrobial activity was achieved in culture on medium AH4 containing soybean meal and glucose, at 30oC and pH 7.0.